The perspectives of family policy in Russia amid increasing cohabitation - Ekaterina Mitrofanova; Alyona Artamonova (European Journal of Government and Economics (EJGE), 2016)
Russia has long been characterized by early and universal marriage. After the Soviet Union collapse, the average age of marriage has been rising, and cohabitations have become common. Many scholars explain the causes of this trend through the perspective of the Second Demographic Transition. The aim of this research was to define the nature of cohabitations in Russia, reveal the factors of entrance to non-marital unions in order to discuss how and why non-marital union is implicated in recent dialogues about family policy. In order to achieve the aim, such methods as Event History Analysis and Sequence Analysis were used.
Keywords: 330; first matrimonial unions; life course; family policy; Event History Analysis; Sequence Analysis.